2019
DOI: 10.1016/j.pmedr.2019.100822
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes increases the risk of depression: A systematic review, meta-analysis and estimates of population attributable fractions based on prospective studies

Abstract: We aim to examine the relationship between diabetes and depression risk in longitudinal cohort studies and by how much the incidence of depression in a population would be reduced if diabetes was reduced. Medline/PubMed, EMBASE, PsycINFO, and Cochrane Library databases were searched for English-language published literature from January 1990 to December 2017. Longitudinal studies with criteria for depression and self-report doctors' diagnoses or diagnostic blood test measurement of diabetes were assessed. Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 70 publications
5
71
3
6
Order By: Relevance
“…A systematic review with meta-analysis of 11 longitudinal studies showed that, compared with individuals without diabetes, people with type 2 diabetes have a 24% increased risk of developing depression [23]. A later systematic review with meta-analysis of 16 longitudinal studies reported a higher pooled OR for incident depression among respondents with diabetes (1.34, 95% CI 1.14-1.57, v 2 = 76.65, I 2 = 80.4%; P < 0.001), again confirming diabetes as a risk factor for depression [24]. Nefs et al [25] conducted a 3-year longitudinal study of 2460 people with type 2 diabetes and ª 2020 Diabetes UK examined the course (incidence, recurrence/persistence) of depressive symptoms by self-report questionnaire in a primary care setting.…”
Section: Depression In Diabetes: Results From Prospective Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…A systematic review with meta-analysis of 11 longitudinal studies showed that, compared with individuals without diabetes, people with type 2 diabetes have a 24% increased risk of developing depression [23]. A later systematic review with meta-analysis of 16 longitudinal studies reported a higher pooled OR for incident depression among respondents with diabetes (1.34, 95% CI 1.14-1.57, v 2 = 76.65, I 2 = 80.4%; P < 0.001), again confirming diabetes as a risk factor for depression [24]. Nefs et al [25] conducted a 3-year longitudinal study of 2460 people with type 2 diabetes and ª 2020 Diabetes UK examined the course (incidence, recurrence/persistence) of depressive symptoms by self-report questionnaire in a primary care setting.…”
Section: Depression In Diabetes: Results From Prospective Studiesmentioning
confidence: 91%
“…A systematic review with meta‐analysis of 11 longitudinal studies showed that, compared with individuals without diabetes, people with type 2 diabetes have a 24% increased risk of developing depression . A later systematic review with meta‐analysis of 16 longitudinal studies reported a higher pooled OR for incident depression among respondents with diabetes (1.34, 95% CI 1.14–1.57, χ 2 = 76.65, I 2 = 80.4%; P < 0.001), again confirming diabetes as a risk factor for depression . Nefs et al .…”
Section: What We Now Know After 25 Years Of Research Into Diabetes Anmentioning
confidence: 91%
“…Both depression and diabetes are highly prevalent, often co-occurring diseases that are among the major causes of global disability. [1][2][3] Comorbid diabetes and depression are associated with a worse prognosis of both diseases, including a higher rate of complications of diabetes, greater disability and an increased risk of mortality. 4 Vulnerable populations, including low-income, low health literacy and ethnic minority individuals experience higher prevalences and worse outcomes for both diabetes and depression.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The number of new cases of depression increased from 17.2 million in 1990 to 25.8 million in 2017 [9]. Over 9.5 million of global depression cases are attributable to diabetes [10]. The occurrence of depression in people with diabetes mellitus is about two to three times higher compared to the general population [11][12][13].…”
Section: Introductionmentioning
confidence: 99%